Digital poisons. (Economist, 2023)
The article discusses the threats facing machine-learning or modern artificial-intelligence (AI) systems, particularly the cyber-attack called data poisoning. The attack involved modifying or adding extraneous information to AI data sets to make its algorithms learn harmful or undesirable behaviours. Also cited is how the rise of generative AI tools like ChatGPT and the image-making system DALL-E 2 makes data poisoning easier to implement.